A new study for aeroplane wing shapes made of boron nitride nanotubes-reinforced aluminium, Part I: review, dynamical analyses and simulation. (1st January 2023) - Gia Ninh, Dinh; Trong Long, Nguyen; Van Vang, Tran; Hoang Ha, Nguyen; Thanh Nguyen, Cong; Viet Dao, Dzung
Graphical abstract: Highlights: The building of aircraft wing shape structures made of advanced materials by an analytical approach. The effects of the change of the aircraft wing shapes, materials factors and thermal environment are considered carefully. The stable and chaotic states of structures are scrutinized through numerical and graphical results. Abstract: A new approach for airplane wing shapes is found in this study with an analytical method. The paper studies the dynamical characteristics of aircraft wing plates using boron nitride nanotube (BNNT) reinforced for aluminium. The distribution of reinforcements through the thickness of the plates is considered to be uniform and functionally graded. The plate profile is defined in terms of a rectangular plate, in which an edge following a function is introduced according to arbitrary functions such as linear, circular, or hyperbolic functions. Equations of motion using geometric nonlinearities defined by von Karman-Donnell and theory of elasticity with applying Galerkin's method is used to obtain the dynamic and chaotic properties of the structure. The achieved results are validated with the previous documents and the finite element analyses (FEA) for fundamental frequencies to confirm the accuracy and reliability of the calculation method in this paper. The influence of the thermal environment, the volume of BNNT, the distribution pattern of reinforcement, as well as geometrical parameters are scrutinized in this paper. The research results show the superior properties of BNNT materials in reinforcing aircraft wings.